Concept analysis of emotion control among schizophrenia - Rahman, Ainun Najib Febrya; Dwidiyanti, Meidiana; Wijayanti, Diyan Yuli; Rahmawati, Ashri Maulida (Universitas Aisyah Pringsewu, 2020)
Emotional control in schizophrenia patients is closely related to the patient's ability to control his negative emotions. Negative emotions in question are feelings of anger, fear and sadness. In the United States about 1.5 million crime cases occur each year. These events are mostly carried out by schizophrenic patients due to their inability to control negative emotions. The purpose of this article is to describe the methodological analysis used to clarify the concept of emotional control in schizophrenia patients. The concept analysis procedure from Walker and Avant is used in this paper. Literature review is carried out using online databases such as Google Scholar, Science Direct, and EBSCHO with keywords of concept analysis, emotional control, and schizophrenia. Antecedents of the concept of emotional control in schizophrenia: self control, mental boundaries, and self determination. Concept attributes: situation selection, situation modification, attentional deployment, cognitive change, and response modulation. The consequences of the concept: success in controlling emotions, happiness, positive results, and leadership effectiveness. Abstrak: Kontrol emosi pada pasien skizofrenia sangat berkaitan dengan kemampuan pasien dalam mengontrol emosi negatifnya. Emosi negatif yang dimaksud adalah perasaan marah, takut dan sedih. Di Amerika Serikat sekitar 1,5 juta kasus kejahatan terjadi setiap tahunnya. Kejadian tersebut banyak dilakukan oleh pasien skizofrenia akibat dari ketidakmampuan dalam mengontrol emosi negatifnya. Tujuan dari artikel ini adalah untuk menggambarkan analisis metodologi yang digunakan untuk memperjelas konsep kontrol emosi pada pasien skizofrenia. Prosedur analisis konsep Walker dan Avant digunakan dalam penulisan ini. Literature review dilakukan menggunakan database online seperti Google Scholar, Science Direct, dan EBSCHO dengan kata kunci analisis konsep, kontrol emosi, dan skizofrenia. Antecedent dari konsep kontrol emosi pada skizofrenia: pengendalian diri, batas mental, dan self determination. Atribut konsep: situation selection, situation modification, attentional deployment, cognitive change, dan response modulation. Konsekuensi dari konsep: keberhasilan mengontrol emosi, kebahagiaan, hasil positif, dan efektifitas kepemimpinan.